2019
DOI: 10.3389/fphys.2018.01967
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ocean Acidification on the Energy Metabolism and Antioxidant Responses of the Yesso Scallop (Patinopecten yessoensis)

Abstract: Ocean acidification (OA), which is caused by increasing levels of dissolved CO2 in the ocean, is a major threat to marine ecosystems. Multiple lines of scientific evidence show that marine bivalves, including scallops, are vulnerable to OA due to their poor capacities to regulate extracellular ions and acid-based status. However, the physiological mechanisms of scallops responding to OA are not well understood. In this study, we evaluated the effects of 45 days of exposure to OA (pH 7.5) on the energy metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 75 publications
(95 reference statements)
1
18
0
Order By: Relevance
“…Our results show that exposure to pH 7.6 increased superoxide production as compared to the two other pH treatments (Figure 5). This is consistent with the available literature, mostly on mollusks, showing that decreased pH can stimulate oxidative stress in the marine organism through increased ROS production (Tomanek et al, 2011;Wang et al, 2016;Sun et al, 2017;Cao et al, 2018;Liao et al, 2019). Enhanced production of ROS such as superoxide ions and hydrogen peroxide were observed under various environmental challenges in marine invertebrates (Liu and Chen, 2004;Hannam et al, 2010;Hernroth et al, 2012;Wang et al, 2016;Sun et al, 2017;Cao et al, 2018).…”
Section: Figure 3 |supporting
confidence: 91%
“…Our results show that exposure to pH 7.6 increased superoxide production as compared to the two other pH treatments (Figure 5). This is consistent with the available literature, mostly on mollusks, showing that decreased pH can stimulate oxidative stress in the marine organism through increased ROS production (Tomanek et al, 2011;Wang et al, 2016;Sun et al, 2017;Cao et al, 2018;Liao et al, 2019). Enhanced production of ROS such as superoxide ions and hydrogen peroxide were observed under various environmental challenges in marine invertebrates (Liu and Chen, 2004;Hannam et al, 2010;Hernroth et al, 2012;Wang et al, 2016;Sun et al, 2017;Cao et al, 2018).…”
Section: Figure 3 |supporting
confidence: 91%
“…During prolonged hypoxic exposure, however, anaerobic degradation of glycogen could be considered another major adaptive mechanism that contributes to longer survival during sustained environmental hypoxia (63,64,73,79). Several works reported that decreased pH alone or synergistically, either with increased temperature or with low oxygen tension, induces anti-oxidative response in marine bivalves (42,57,96), while Tomanek (99) and Sokolova (85) further discuss the possible mechanisms leading to mitochondrial ROS formation during exposure of mussels to elevated CO 2 and low pH i . The voluntary switch to anaerobiosis in bivalves may serve as a mechanism reducing ROS formation, thus resulting to longer survival (3,27).…”
Section: R272 Mussel Gene Expression and Cellular Stress Responsementioning
confidence: 99%
“…We also observed downregulation of genes associated with oxidation-reduction processes (Figures 4 & S3), which, in conjunction with downregulation of electron transport, may reflect a dampened immune system. The electron transport chain is a site that produces reactive oxygen species, which are an important internal defense mechanism, but which need to be controlled by antioxidant enzymes (Cao et al, 2018; Liao et al, 2018). Downregulation of genes associated with oxidation-reduction may deplete the availability of antioxidants to counteract reactive oxygen species, thereby overwhelming the antioxidant defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%